Deimatic or aposematic?. (March 2016) - Skelhorn, John; Holmes, Grace G.; Rowe, Candy
Highlights: In a recent paper Umbers & Mappes redefined deimatic displays. We argue that their definition and previous definitions lack clarity. We suggest a definition based on the mechanisms via which displays prevent predation. To ascertain whether a display is deimatic one must observe its affects on predators.